Determining students’ speaking skill based on guessing game at the eighth grade of SMP Negeri 2 Lolofitu Moi - Waruwu, Asirida; Harefa, Afore Tahir; Telaumbanua, Kristof Martin Efori; Zebua, Elwin Piarawan (Institute of Computer Science (IOCS), 2025)
This research entitled “Determining Students’ Speaking Skill Based on Guessing Game at the Eighth Grade of SMP Negeri 2 Lolofitu Moi” aims to determine students’ speaking skill levels and the factors influencing them through the use of a guessing game. This study employed a qualitative descriptive method with data collected from observation and interviews with students and an English teacher. The results showed that most students were at the basic speaking level, able to produce simple sentences but still made errors in pronunciation, grammar, and vocabulary. The guessing game made learning more interactive and enjoyable, increased students’ confidence, and encouraged active participation. However, challenges such as limited vocabulary and fear of mistakes remained. It can be concluded that guessing games effectively improved students’ motivation and speaking confidence, although further practice is needed to enhance fluency and accuracy.